ChemInform Abstract: High‐Nuclear Vanadoniobate Nb48V8 Multiple‐Strand Wheel. Issue 7 (January 2016) - Zhang, Yu‐Teng; Qin, Chao; Wang, Xin‐Long; Huang, Peng; Song, Bai‐Qiao; Shao, Kui‐Zhan; Su, Zhong‐Min
Abstract: The new compound Na18 [Nb48 V8 (OH)30 O130 ] ·33H2 O is synthesized by reaction of K7 HNb6 O19, VCl3, and NaOH (H2 O, 70—75 °C, 5 h, 42% yield).